Protective Effects Of Garlic Extract Against Chromium Induced Genotoxicity In Bone Marrow Cells Of Mice - MOSHI RAJU M; MINNY JAEL. P; K. RUDRAMA DEVI (International Journal of Pharma and Bio Sciences, 2012)
The protective effect of garlic extract in chromium induced genotoxicity was evaluated using analysis of chromosomal aberrations in somatic cells of mice in in vivo animal model. Three doses of garlic extracts were selected for modulation and administered to animals after priming with chromium all the animals were killed after 24 hrs of treatment and the mitotic preparations were made. A significant decrease was observed in the percentage of chromosomal aberrations when animals primed with garlic extract. The present results clearly indicate the protective nature of garlic extract against heavy metal genotoxicity.